EquationsMenu1What Is an Equation?2Equations Activities 13Remove Number in Front of x4Equations Activities 25Remove Number Under x6Equations Activities 37Equations with Several Terms on Both Sides8Equations Activities 49Equations with Fractions and Parentheses10Equations Activities 5 5.1) Solve the equations: a) 3 + x 4 − 5 = 2x − 3 b) 2 + 2x 3 + 4 = x − 3 2 − 7 c) x 7 − 20 + x = x + 2 3 + 11 d) 21 + 2x 5 + 12 = 22 − 2x 3 e) 3x 8 + 13 − 2x = −12 + 3x 16 f) 23 − 3x + 4x − 1 3 = 9 + 21x 4 a) 3 + x 4 − 5 = 2x − 3 b) 2 + 2x 3 + 4 = x − 3 2 − 7 c) x 7 − 20 + x = x + 2 3 + 11 d) 21 + 2x 5 + 12 = 22 − 2x 3 e) 3x 8 + 13 − 2x = −12 + 3x 16 f)23 − 3x + 4x − 1 3 = 9 + 21x 4 5.2) Solve the equations: a) x(7 − 5) = 4 b) 2(x − 1) = 6 c) 3(x + x) = 12 d) 3 (1 2 − x) = 2(x + 1) e) 4(2x + 5) = 5x + 38 f) 12 (x 3 + 2x 4 ) = −5(3x − 20) g) 2 5 + 10x − 1 = 3(3x − 2) h) 6x (4 − 2 3) = 9(3x + 7) a) x(7 − 5) = 4 b) 2(x − 1) = 6 c) 3(x + x) = 12 d) 3 (1 2 − x) = 2(x + 1) e) 4(2x + 5) = 5x + 38 f) 12 (x 3 + 2x 4 ) = −5(3x − 20) g) 2 5 + 10x − 1 = 3(3x − 2) h) 6x (4 − 2 3) = 9(3x + 7) You can find the solutions here. Want to know more?Sign UpIt's free!DoneContinue11Equations with x in the Denominator12Equations Activities 613Checking the Answer14Equations Activities 715How to Solve Power Equations16Equations Activities 817Systems of Equations (Graphing)18Systems of Equations (Substitution)19Systems of Equations (Elimination)20Equations Activities 921Equations Solutions
5.1) Solve the equations: a) 3 + x 4 − 5 = 2x − 3 b) 2 + 2x 3 + 4 = x − 3 2 − 7 c) x 7 − 20 + x = x + 2 3 + 11 d) 21 + 2x 5 + 12 = 22 − 2x 3 e) 3x 8 + 13 − 2x = −12 + 3x 16 f) 23 − 3x + 4x − 1 3 = 9 + 21x 4 a) 3 + x 4 − 5 = 2x − 3 b) 2 + 2x 3 + 4 = x − 3 2 − 7 c) x 7 − 20 + x = x + 2 3 + 11 d) 21 + 2x 5 + 12 = 22 − 2x 3 e) 3x 8 + 13 − 2x = −12 + 3x 16 f)23 − 3x + 4x − 1 3 = 9 + 21x 4 5.2) Solve the equations: a) x(7 − 5) = 4 b) 2(x − 1) = 6 c) 3(x + x) = 12 d) 3 (1 2 − x) = 2(x + 1) e) 4(2x + 5) = 5x + 38 f) 12 (x 3 + 2x 4 ) = −5(3x − 20) g) 2 5 + 10x − 1 = 3(3x − 2) h) 6x (4 − 2 3) = 9(3x + 7) a) x(7 − 5) = 4 b) 2(x − 1) = 6 c) 3(x + x) = 12 d) 3 (1 2 − x) = 2(x + 1) e) 4(2x + 5) = 5x + 38 f) 12 (x 3 + 2x 4 ) = −5(3x − 20) g) 2 5 + 10x − 1 = 3(3x − 2) h) 6x (4 − 2 3) = 9(3x + 7) You can find the solutions here. Want to know more?Sign UpIt's free!DoneContinue